Characteristics of selected social campaigns in the prevention of testicular cancer - Stępień, Maciej; Woynarowska-Sołdan, Magdalena; Badowska-Kozakiewicz, Anna (Medical Studies/Studia Medyczne, 2023)
Testicular cancer is a serious health problem for men, especially young men. Diagnosing the cancer and starting treatment at an early stage is associated with a high probability of cure. Therefore, from an individual and public health point of view, prompt diagnosis is important. This can be achieved, among other things, through testicular self-examination as a basis for secondary prevention. Social campaigns, i.e. targeted communication activities aimed at solving or reducing social problems by modifying the attitudes or behaviour of specific audiences, can be a tool to encourage men to self-examine. Social campaigns on testicular cancer prevention carried out in Poland include “Odważni wygrywają”, “Mosznowladcy”, “Łap jaja!” and “BadajJAJKA”. These issues have been present in the public space over the past few years. All campaigns had specific slogans, reach, partners, audiences, purpose and used specific tools. Only for some of them could evaluation data be found on their progress and results.